Impact of the audit committee on audit fees: A review and future research agenda - Michail Nerantzidis; Andreas Koutoupis; George Drogalas; Christina Vadasi; Dimitrios Mitskinis (Cogent Business & Management, 2023)
Over the last decades, research on the relationship between audit committees (ACs) and audit fees (AFs) has been increasing. Although numerous scholars have studied this topic, to the best of our knowledge, there is no systematic literature review (SLR) that provides a synthesized state of knowledge regarding this research area. To fill this gap this study presents a comprehensive systematic and objective review of existing research on the interaction between ACs and AFs. Using a sample of 78 articles, we find that most studies are empirical and country-specific and focus on developed markets in Europe and America. We also find that the majority of the examined papers use quantitative research methods by employing demand and supply theory either implicitly or explicitly. Further, we develop a categorization scheme, allocating the previous studies to six research themes (i.e. Composition, Diligence, Discrimination, Disclosure, Presence of (strong) AC and Compensation) and ten sub-themes. We then analyze each theme and its sub-themes providing details regarding its importance and impact on AFs and show that Diligence and Discrimination remain underexplored. Finally, we outline some potentially fruitful avenues for future research.
Keywords: 650; audit committee; audit fees; audit quality; remuneration; systematic literature review